The Effect of Footing Shape on the Elastic Modulus of Soil - Pantelidis, Lysandros (My University, 2022)
In practice, geotechnical engineers often use triaxial elastic soil property values derived from the corresponding test or continuous probing test results (e.g. Cone Penetration Test), even for structures deforming under plane strain conditions, such as strip footings. Review of the available theoretical and experimental studies, however, led to the following observations: the triaxial elastic modulus differs from the respective plane strain one and in addition to the aspect ratio of footing, the soil modulus depends on the thickness of the soil medium. Based on experimental findings and on the elastic theory and using a sequential way of thinking, the elastic settlement at the centre of a B × L footing is suggested that be calculated considering the respective B × B footing along with the original distributed loading value.
Keywords: Plane strain conditions; Modulus of elasticity; Footing shape; Elastic settlement; Winkler’s spring analysis; Shallow foundations